Evaluating multi-scale precipitation forecasts using high resolution analysis - C. Wittmann; T. Haiden; A. Kann (Advances in Science and Research, 2010)
The SAL (Structure, Amplitude, Location) method is used for verification of precipitation forecasts at horizontal grid spacings ranging from 2.5 km to 25 km, using a high-resolution 1 km precipitation analysis as a reference. The verification focuses on a summertime period with predominantly convective precipitation. The verification domain contains lowland as well as alpine areas. Evaluation of the individual SAL components shows that with regard to area mean values (A) the benefit of high resolutions models becomes apparent only in high impact weather situations. For the summertime period studied, the subjective impression of better structured precipitation fields (S) in higher resolution models can generally be confirmed. The most significant improvement appears to be associated with explicit simulation of deep convection.